Pembelajaran Kooperatif sebagai Strategi Peningkatan Keterampilan Membaca Bahasa Arab di Pesantren - Nurul Fauzah (Global Education Journal, 2026)
Arabic reading instruction in Islamic boarding schools (pesantren) continues to face several challenges, including limited vocabulary mastery, difficulties in comprehending sentence structures, low levels of students' active participation, and the predominance of teacher-centered instructional approaches. Although cooperative learning has been widely examined in language education, studies that specifically position it as a strategy for enhancing Arabic reading skills within the pesantren context remain relatively limited. This study aims to analyze the implementation of cooperative learning as a strategy for improving the Arabic reading skills (mahārah qirā’ah) of students in an Islamic boarding school. Employing a descriptive qualitative approach with a case study design, the research involved 30 first-year senior secondary (Aliyah) students at Darullughah Wadda’wah Islamic Boarding School. Data were collected through classroom observations, semi-structured interviews, field notes, and instructional documentation, and were analyzed using data reduction, categorization, interpretation, and conclusion drawing. The findings reveal that cooperative learning enables students to comprehend vocabulary in context, identify main ideas and detailed information, increase classroom participation, strengthen self-confidence, and foster peer-assisted learning. The study's analytical contribution lies in demonstrating that cooperative learning should be understood not merely as a group-work technique but as a pedagogical framework that integrates social constructivism, peer scaffolding, and the pesantren tradition of collective learning to strengthen Arabic reading proficiency (mahārah qirā’ah).